ЁШЛАРНИНГ ИЖТИМОИЙ ФАОЛЛИГИНИ ОШИРИШДА ҒОЯВИЙ ТАРБИЯНИНГ АҲАМИЯТИ - Базаров, О. (SCIENCE and SOCIETY, 2020)
In the article, we study various situations occurring in the modern period of globalization, their impact on the education of young people, issues of ideological education and problems in the process of ideological education.